2020
DOI: 10.1007/s13201-020-01230-2
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal pollution index for assessment of seasonal groundwater supply quality in hillside area, Kalasin, Thailand

Abstract: Agriculture is a major activity in most rural areas in northern Thailand. The aim of this study was to assess the heavy metal pollution index (HPI) for water supply quality in a rural village in Kalasin Province named Kaeng Ka-am village located in the hillside area of Phu Phan mountain. The concentration of heavy metals including iron (Fe), manganese (Mn), and zinc (Zn) in groundwater supply has been analyzed by the atomic absorption spectrometer. The groundwater supplied samples were collected from eight dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 8 publications
2
6
1
Order By: Relevance
“…According to Kim et al (2002), the pH of this range may be attributed to the effects of bicarbonates, geology of the area and the buffering capacity of the water system. This result is in line with those reported by Koffi et al (2014) and Mohamed and Zahir (2013) at Ivory Coast and India, respectively, but higher than the value 5.0 and 5.2 reported by Chiamsathit et al (2020) from Thailand. The values of electrical conductivity of water in the dry season were generally higher than the wet season; however, statistical analysis showed that the means were not different (p > 0.05) from each other.…”
Section: Physicochemical Parameters Analyzedsupporting
confidence: 93%
See 2 more Smart Citations
“…According to Kim et al (2002), the pH of this range may be attributed to the effects of bicarbonates, geology of the area and the buffering capacity of the water system. This result is in line with those reported by Koffi et al (2014) and Mohamed and Zahir (2013) at Ivory Coast and India, respectively, but higher than the value 5.0 and 5.2 reported by Chiamsathit et al (2020) from Thailand. The values of electrical conductivity of water in the dry season were generally higher than the wet season; however, statistical analysis showed that the means were not different (p > 0.05) from each other.…”
Section: Physicochemical Parameters Analyzedsupporting
confidence: 93%
“…According to WHO (1996), the concentration of TDS in water from natural sources varies from 30 to 600 mg/L depending on the solubility of minerals in the different geological regions. The results of TDS in this study are similar to those reported by Amfo-Out et al (2012) at the Ga East Municipality of Ghana but higher than those reported by Chiamsathit et al (2020) from Thailand.…”
Section: Physicochemical Parameters Analyzedsupporting
confidence: 90%
See 1 more Smart Citation
“…Bonferroni pairwise multiple comparisons showed no significant difference (p > 0.05) between the main water sources and their controls. The results of pH values in all sources of water in this study were higher than those reported by Chiamsathit et al (2020) in Thailand. The mean conductivity of the water samples ranged from a minimum of 246.8±88.9µS/cm (borehole) to a maximum of 4618.9±673.0µS/cm (Seawater).…”
Section: Physico-chemical Parameters Of Watercontrasting
confidence: 87%
“…Percentage Figure (4) shows that 93.8% of respondents reported that death of infants was increased while only 6.2% of them who were reported that it was decreased. This result was agreed with (Bruederle A. and Hodler R. 2019).…”
Section: Newly Born Childern Defectsmentioning
confidence: 99%